Análisis Comparativo De Herramientas Forenses Informáticas Para La Realización De Peritajes En Medios Digitales - Iván Mesias Hidalgo-Cajo; Saul Yasaca-Pucuna; Byron Geovanny Hidalgo-Cajo; Keylee Alexandra Cevallos-Paredes; Diego Patricio Hidalgo-Cajo; Víctor Manuel Oquendo-Coronado (European Scientific Journal, ESJ, 2018)
This paper focuses on making a comparison of the different computer forensic tools used in the performance of data surveys in digital media. The research was developed based on the method of weighting by criteria (scientific and descriptive study). In this study, specifically four computer forensic tools were used and evaluated by six criteria for the selection of them, and they were chosen based on ISO 9126:1998. Based on the comparison, the results of the four computer forensic tools were analyzed. It was determined that for the different criteria (Case study: Clone of 500 Gb hard disk in off mode), the HD Clone and XWay Forensics tools obtained 84.62% of acceptability, compared to Norton Ghost that obtained a contribution of 69.23% and the tool EnCase with a score of 58.46% to obtain the cloning of the disks. In addition, with the use of ISO 9126: 1998, greater portability, reliability of the results, acquisition cost of the tool, ease of use and application, greater operational capacity and support for the tool was achieved in the cloning of digital media. This is attributed to the fact that it is composed of six evaluation criteria as mentioned above.